METHODS OF CALCULATING THE DYNAMICS OF SLUDGE SEDIMENTS IN WATER DELIVERY CHANNELS OF PUMPING STATIONS - Bobojonov Nurimon Shaxriyor-o‘g‘li (American Journals, 2024)
In this article, the fractional composition of turbidity and the dynamics of turbid sediments in the channel that brings water to the 1st pumping station of the Karshi main channel are studied.
Keywords: Amudarya, water intake without dam, Uzan, deformation, pump.